If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -4a + -6 = 0 Reorder the terms: -6 + a + -4a = 0 Combine like terms: a + -4a = -3a -6 + -3a = 0 Solving -6 + -3a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3a = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3a = 0 + 6 -3a = 0 + 6 Combine like terms: 0 + 6 = 6 -3a = 6 Divide each side by '-3'. a = -2 Simplifying a = -2
| 50d+33-37d=46 | | -2x+10=18x-30 | | x+(x+22)=150 | | 38=6-2z | | 2/7x=72 | | r=9c-d/c | | 2*6-1y=18 | | 50/x=1250/425 | | -(8y-5)-(-7y+8)=6 | | 2x^2-18xy+16y^2=0 | | 2*20-1y=18 | | 7x-22=-6+5x | | 4n+8n=9n-7 | | 13/21=299/x | | 2*4-1y=18 | | 16x^2+32x+16=0 | | r=9c-d | | 18x^2-32+12=0 | | 7x-16=-37+4x | | 4(-x+6)=20 | | 512^2/3 | | (2x+7y-4z)-(5x+3y-8z)= | | c^2-4=-3c | | x/6150=65/82 | | 5x=76 | | h(x)=4x^2+12x-40 | | 4y=116 | | 6*50= | | 6x+2=-4x+10 | | -25=9x+2 | | 2x+3x^2=10 | | 0=11x^2-64x+45 |